Influencer marketing: The impact of disclosing sponsorship compensation justification on sponsored content effectiveness. Issue 2 (20th May 2019) - Stubb, Carolina; Nyström, Anna-Greta; Colliander, Jonas
Abstract : Purpose: The purpose of this paper is to investigate the effects of a particular form of sponsorship disclaimer in sponsored content by social media influencers (SMIs), namely a sponsorship compensation justification disclosure. A sponsorship compensation justification disclosure explains why influencers and brands engage in sponsorship collaborations by providing a normative reason that justifies the existence and dissemination of sponsored content. Design/methodology/approach: An experimental design was used to compare the effects of a sponsorship compensation justification disclosure made by either an influencer or the sponsoring brand, to a simple sponsorship disclosure and a no disclosure control post, on consumers' responses to a product-review video by a YouTube influencer. Findings: The paper offers empirical evidence that sponsorship compensation justification generates more positive consumer attitudes toward influencers receiving sponsorship compensation, and increases source and message credibility, compared to a simple sponsorship disclosure. Research limitations/implications: The hypotheses were tested on one YouTube video, comprising of a single product category, one SMI and one social media platform. Further studies might replicate the experiment on different product categories and on different social media platforms. Practical implications: This empirical study can offer brand communication managers and influencers important information on how to communicate and design sponsorship disclosures to reach-desired responses from consumers. Originality/value: The study is the first study to empirically demonstrate the effects of this particular type of sponsorship disclosure.